The Effects of Natural Weathering on Color Stability of Impregnated and Varnished Wood Materials - Turkay Turkoglu; Ergun Baysal; Hilmi Toker (Advances in Materials Science and Engineering)
The aim of this study was to investigate effects of natural weathering on color stability of Scots pine (Pinus sylvestris L.) and Oriental beech (Fagus orientalis L.) impregnated with some chemicals [tanalith-E (TN-E), adolit-KD5 (AD-KD5), and chromated copper arsenate (CCA)] and then varnished [synthetic varnish (SV) and polyurethane varnish (PV)]. While applying varnish increased lightness, impregnation decreased lightness of the wood specimens before natural weathering. Natural weathering caused greenish, bluish, and dark color tones of the wood surface. Total color change was increased with increasing exposure times in natural weathering. Untreated (control) wood specimens exhibited higher color changes than the other wood specimens in all the stages of natural weathering. The total color changes of untreated Oriental beech specimens were less than untreated Scots pine specimens. The color stability of impregnated and varnished wood specimens gave better results than untreated and solely varnished wood specimens after natural weathering. The best color stability was obtained from both Oriental beech and Scots pine wood impregnated with TN-E before PV coating.